Romance Clitics and the Structure of AGRP - Motapanyane, Virginia (Linguistica Atlantica, 1992)
This paper proposes a development of the analysis in Kayne (1990), where clitic movement is related to the projection of an abstract lN FL(ectional)-head, compatible with infinitive (i.e. non-tensed) clauses. It will be argued, on the basis of Romanian data, that this abstract iNFL-head is present in tensed clauses as well, and that it can be defined as part of the Agreement Phrase (AGRP). This proposal is extended to other Romance languages leading to a uniform account of clitic movement to INFL.